Effect on various electrode materials in treating spent caustic wastewater using bioelectrochemical cell (BeCC) - Tengku Indok Munirah, Daeng Yacob (2017)
Spent caustic is an industrial wastewater that is generated from petroleum refineries and it is the most difficult of all industrial wastes to dispose or treat properly. In this study, treatment of wastewater using bioelectrochemical cell (BeCC) seems to be promising technology to treat spent caustic because it shows efficient treatment besides recovery energy. Principally, the voltage generated will depend on various factors including the electrode material performance. Therefore, the great significance is to select and develop suitable electrode materials to promote the efficiency of BeCC. The objectives of this study are to investigate the performance of BeCC towards removal efficiency; namely chemical oxygen demand (COD) and sulphide. Next is to access the performance of BeCC on electricity generation by using different type of electrode materials and to study the effect on surface of various electrode materials by analyse using scanning electron microscopy to get SEM image. A reactor of BeCC was operated under ambient conditions. Spent caustic wastewater samples from industry is collected and entered with the flowrate of 0.2 L/d into BeCC for treatment and treated for 3 weeks. The great treatment efficiency for COD in BeCC is achieved 94% removal using carbon-carbon electrode at constant hydraulic retention time (HRT) of 20 days. The various combinations of anode and cathode material is studied and the maximum voltage of 189.1mV is generated when spent caustic samples is treated using carbon-carbon electrode, while 153.7mV generated using copper-carbon electrode and minimum voltage of 125.1mV is generated using aluminium-carbon electrode. After that, surface of each electrode is analyzed using SEM-EDX to investigate the morphological properties of the anode and cathode surface before and after operation and show that there are microorganism attachment on the surface of electrode. Thus, the suitable combination of electrodes can be determined. Finding shows that electrode combination of carbon-carbon is the best since it gives high COD and sulphide removal, instead of high voltage generated.